Synthesis of a New Polyfunctionalised Pyrimidine-4-carboxylate and Its Application for the Construction of a Series of Pyrimidine Derivatives - Gonçalves, Davana S.; Silva, Michael J. V.; Souza, Thiago F.; Jacomini, Andrey P.; Back, Davi F.; Basso, Ernani A.; Moura, Sidnei; Rosa, Fernanda A. (Synthesis, 2016)
The synthesis of a new and versatile polyfunctionalised pyrimidine-4-carboxylate, along with the study of its reactivity against 1,2-dinucleophiles and 1,4-dinucleophiles, is reported. These simple and efficient methodologies allowed for the synthesis of novel pyrimidine derivatives such as pyrimido[4,5-d]pyridazin-8-one-5-carboxylates and their corresponding carbohydrazides and N-acylhydrazone (NAH) derivatives, pyrimido[4,5-d][1,2]oxazin-8-one and its corresponding carbohydrazide derivative, and 3-pyrimidinylquinoxaline-2-one and its corresponding carbohydrazide. Furthermore, pyrimidine hydroxyimino derivatives were also prepared.
Keywords: pyrimidine-4-carboxylate; 2,4,5-trisubstituted pyrimidine; pyrimido[4,5-d]pyridazinone; pyrimido[4,5-d]oxazinone; quinoxalinone